An Additive Rotational Perturbation Technique for Privacy Preserving Data Mining - et. al., Sangeetha Mariammal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the usage of internet and web applications emerges faster, security and privacy of the data is the most challenging issue which we are facing, leading to the possibility of being easily damaged. The privacy preservation techniques like condensation, randomization and tree structure etc., are having limitations, they are not able to maintain proper balance between the data utility and privacy and it may have the problem with privacy violations. This paper presents an Additive Rotation Perturbation approach for Privacy Preserving Data Mining (PPDM). In this proposed work, various dataset from UCI Machine Learning Repository was collected and it is protected with a New Additive Rotational Perturbation Technique under Privacy Preserving Data Mining. Experimental result shows that the proposed algorithm’s strength is high for all the datasets and it is estimated using the DoV (Difference of Variance) method.